CORRELATION BETWEEN SELF-ESTEEM AND SOCIAL WELL-BEING OF UNDERGRADUATES IN ENUGU STATE - Ugwu, Kelechi T. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Well-being is a fundamental component of human beings' overall health, enabling them to overcome difficulties and achieve the desired goal successfully. Well-being is a multidimensional construct that includes social well-being. The present study aimed to investigate social well-being variation among undergraduates in Enugu state based on self-esteem. In the study, two hundred and twenty undergraduates enrolled in four public tertiary institutions in Enugu State, Nigeria, were recruited. The male and female students were conveniently pooled from different departments in the selected institutions. The respondents completed a self-report measure of the Rosenberg Self-Esteem Scale (RSES) and The Social Well-being Scale. A simple linear regression model was deployed to test the study's formulated hypothesis. The result showed that social support statistically significantly predicted the social well-being of the undergraduates. The study concludes that self-esteem is an essential determinant of an undergraduate's social well-being. The result has implications for enhancing the social well-being of undergraduates.